The Daily Press Fashions a Heroic Intellectual: The Making of Florentino Ameghino in Late Nineteenth‐Century Argentina. (August 2016) - Podgorny, Irina
Abstract: This article considers the emerging career of school preceptor Florentino Ameghino (1854?–1911), a fossil collector from the Argentine countryside who became an international authority in the 1880s and 1890s in the field of prehistory and the paleontology of vertebrates. Reflecting on investigations in the 1870s about the antiquity of humanity in the Argentine Pampas, Ameghino's story allows us to examine how the press circulated news in a context where political and intellectual matters were closely interconnected. This work is based on a collection of newspaper clippings gathered by Ameghino between 1874 and 1897 and found in the Jorge Furt Library, a private collection of books located near Luján, the city where it is said that Ameghino was born.